Linking Forces of Energy Efficiency, Technological Innovation, and Financial Development: Pathway to Economic Recovery in Post-COVID-19 Era and Sustainable Development - Udemba, Edmund Ntom; Chikezie Ekwueme, Daberechi; Philip, Lucy Davou (Springer, 2025)
Our paper examines the strategies for achieving economic recovery from the adverse effects of COVID-19 and outlines a pathway for sustainable economic development in Brazil, one of the emerging economies that suffered economic setbacks due to the pandemic. In the post-COVID-19 era, countries worldwide are actively formulating strategies to recover economically and, in most cases, are aiming for targeted sustainable development. Against this backdrop, we adopt Brazil’s time series data of 2001Q1–2019Q4 to investigate and unveil the best global practice for the quick recovery of the country’s economic development and equally advise on the best policies to engender sustainable economic development of the country. Our analysis focused on policy-rooted instruments (energy efficiency, financial development, and technological innovation). To achieve the objectives of this study, we utilized a novel nonlinear autoregressive distributed lag (NARDL), asymmetric econometric techniques to analyze the data. The findings from our analyses confirm the highlighted objectives of the study and support the application of the selected instruments in economic recovery and the pursuit of sustainable development in Brazil. Specifically, the positive shocks to the energy efficiency of Brazil (LNENFFIC) have a positive impact on its economic development in both the short and long run. Similarly, the positive and negative shocks to Brazil’s financial development (FD) displayed positive and negative impacts on Brazil’s economic progress in both short run and long-term periods. The positive and negative shocks to Brazil’s technological innovation influence its economy in both the long run and short run. These findings emphasize that the instruments selected—energy efficiency, financial development, and technology—are effective in reinvigorating Brazil’s economy. The implications suggest that well-designed policies based on these instruments have the potential to make a significant contribution to Brazil’s economic recovery and long-term sustainable development. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.
Keywords: Brazil; Economic growth; Energy efficiency; Financial development; NARDL; Sustainable development; Technological innovation